Model Development for Health Screening System in Prachin Buri Province - Siriprasert, Rawee; Rochanapraphaphun, Nuchlada (Journal of Health Science of Thailand, 2018)
Diabetes mellitus and hypertension are very important diseases in Thailand. Prevention measures are major topics of concern of the nation and still in developing process. The objective of this action research was to develop health screening system including services for persons in a predisease stage, conducted during May 2007 - December 2008. It was divided into preparation, implementation and evaluation. The preparation phase had two stages, first stage; collection and analysis of health screening policy. Data were collected from documents. In the second stage, designed and developed health screening and grouping tools. In the second phase, implementation was launched in all health centers and hospitals. In the third phase, evaluation, secondary data on screening coverages and lifestyle education service prevalences of prediabetes and prehypertension (via TBH.DB. program in HCIS) were collected and analyzed by descriptive statistics. In an interview, an assessment on satisfaction to health screening tools was made and data was analyzed using content analysis. The result showed that in the first phase, both Ministry of Public Health and National Health Security Office had health screening policies. Health screening and classifying tools included items of blood sugar, blood pressure, waist circumference and body mass index. Target people were classified into white (normal), gray (early abnormal) and black (close to disease). In second phase, implementation was launched in all health centers and hospitals. Third phase, coverage of diabetes screening to 72.2 percent and hypertension 78.7 percent. Prevalence of prediabetes during 2006- 2008 were white group (normal) swinging from 64.6 percent to 62.1 percent and 67.0 percent, gray group slowing downward trend from 30.1 percent to 33.3 percent and 28.2 percent, black group fluctuating from 5.3 percent to 4.6 percent and 4.9 percent. On coverage of prehypertension during 2006 - 2008, the white group increased from 63.5 percent to 66.8 percent and 67.9 percent, gray group decreased from 32.3 percent to 29.7 percent and 28.7 percent, black group decreased from 4.2 percent to 3.5 percent and 3.4 percent. In all, 52.5 percent of gray and black groups had attended to lifestyle change education service. In the fourth phase, the health screening tools was very useful, provided more recognition and concern to screened people. The study suggested that further development of services for predisease will be very helpful for diseases prevention.